2016
DOI: 10.5194/acp-16-2747-2016
|View full text |Cite
|
Sign up to set email alerts
|

Detailed budget analysis of HONO in central London reveals a missing daytime source

Abstract: Abstract. Measurements of HONO were carried out at an urban background site near central London as part of the Clean air for London (ClearfLo) project in summer 2012. Data were collected from 22 July to 18 August 2014, with peak values of up to 1.8 ppbV at night and non-zero values of between 0.2 and 0.6 ppbV seen during the day. A wide range of other gas phase, aerosol, radiation, and meteorological measurements were made concurrently at the same site, allowing a detailed analysis of the chemistry to be carri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 94 publications
(113 reference statements)
11
153
5
Order By: Relevance
“…Correlations of HONO with its precursors are expected to become worse when measurements are carried out above high trees as at the PROPHET site, which are able to fully decouple the ground surface from the air above the canopy (Sörgel et al, 2011a;Foken et al, 2012). The results from the present study are qualitatively also in good agreement with former studies in which the daytime source of HONO was quantified using the PSS approach and in which also a strong correlation of the daytime source with radiation and/or NO 2 was observed (Elshorbany et al, 2009;Sörgel et al, 2011b;Villena et al, 2011;Wong et al, 2012;Lee et al, 2016;Meusel et al, 2016). This observation may imply a mechanism of HONO formation by the reduction of NO 2 with organic photosensitizer materials like humic acids as proposed in laboratory studies (George et al, 2005;Stemmler et al, 2006Stemmler et al, , 2007Han et al, 2016).…”
Section: Correlation Between Fluxes Of Hono and Potential Precursorssupporting
confidence: 90%
See 2 more Smart Citations
“…Correlations of HONO with its precursors are expected to become worse when measurements are carried out above high trees as at the PROPHET site, which are able to fully decouple the ground surface from the air above the canopy (Sörgel et al, 2011a;Foken et al, 2012). The results from the present study are qualitatively also in good agreement with former studies in which the daytime source of HONO was quantified using the PSS approach and in which also a strong correlation of the daytime source with radiation and/or NO 2 was observed (Elshorbany et al, 2009;Sörgel et al, 2011b;Villena et al, 2011;Wong et al, 2012;Lee et al, 2016;Meusel et al, 2016). This observation may imply a mechanism of HONO formation by the reduction of NO 2 with organic photosensitizer materials like humic acids as proposed in laboratory studies (George et al, 2005;Stemmler et al, 2006Stemmler et al, , 2007Han et al, 2016).…”
Section: Correlation Between Fluxes Of Hono and Potential Precursorssupporting
confidence: 90%
“…In these studies, calculated daytime HONO sources, determined from HONO levels exceeding theoretical photostationary state (PSS) values, showed high correlations with the photolysis rate coefficient J (NO 2 ) or the irradiance and NO 2 concentration Su et al, 2008;Elshorbany et al, 2009;Sörgel et al, 2011b;Villena et al, 2011;Wong et al, 2012;Lee et al, 2016;Crilley et al, 2016). However, concentrations are not only controlled by the local ground surfaces source processes but also depend on the convective mixing in the atmosphere, leading to a potential misinterpretation of the correlation results.…”
Section: S Laufs Et Al: Diurnal Fluxes Of Hono Above a Crop Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, model underprediction of HONO mixing ratios in the morning can be one cause for modeled versus measured HO 2 / OH disagreement. Lee et al (2016) indicate that, even after additional gasphase and heterogeneous HONO sources were added to MCMv331, HONO was still underestimated relative to models on average and that a missing HONO source was correlated with J NO 2 , NO 2 , and the product of NO 2 and OH reactivity for an urban area. Furthermore, only model results using measured HONO were able to replicate observed OH levels.…”
Section: Modeled Ambient Hono Sourcesmentioning
confidence: 98%
“…It is known that NO 2 adsorption onto the chamber walls can result in the heterogeneous formation of nitrous acid (HONO) through the reaction of NO 2 with water vapor ad-sorbed onto surfaces (Finlayson-Pitts et al, 2003); a photolytic HONO source has also been previously reported (Rohrer et al, 2005;George et al, 2005;Stemmler et al, 2006;Langridge et al, 2009;Lee et al, 2016;Crilley et al, 2016). During the 2013 DISCOVER-AQ study in Houston, TX, excess HONO of up to 5 times ambient values was measured in the MOPS chambers, which can thus create excess OH and positively bias the MOPS P(O 3 ).…”
Section: Mops Measurementsmentioning
confidence: 99%